Analysis of teacher training needs for peace education in early childhood education (PAUD) - Muhamad Kosim Gifari; Dinn Wahyudin (Inovasi Kurikulum)
In the Indonesian context, peace education is becoming increasingly relevant considering the existing cultural, religious, and ethnic diversity. Teachers are a critical sector and have a significant role in instilling peace education in schools. So, competent skills are needed by every teacher who teaches the students about peace education. Then, this study aims to analyze the need for teacher training in peace education in early childhood education. This study uses a quantitative method with a survey approach to explore the need for teacher training related to peace education in early childhood education (PAUD). Data collection was carried out using a Likert scale-based questionnaire. The population of this study is PAUD teachers of RA Al-Hikam Soreang in the Bandung Regency area. The research respondents were taken using the census technique.  The respondents were 5 (five) people or all teachers of RA Al-Hikam Soreang. This research reveals a significant need to improve teacher training in peace education in early childhood education.